Inhaled foreign bodies in adolescents and adults - S.M. Tariq; J. George; S. Srinivasan (Monaldi Archives for Chest Disease, 2005)
Background. Accidental foreign body inhalation is not uncommon. The incidence is high in children, especially the very young ones. We evaluated the management of inhaled foreign bodies in an adult respiratory medical unit, highlighting circumstances leading to inhalation, associated complications and difficulties encountered at bronchoscopic retrieval. Methods. We reviewed all cases of inhaled foreign bodies presenting over a period of 12 years (1991-2003). Results. 5 of 8 cases were teenagers whereas 3 were aged over 55 years. The older patients had co-morbidities and had aspirated food particles. In 2 cases, a bronchoscopy was performed primarily to exclude lung cancer, and the discovery of a foreign body was a surprise. Pulmonary complications related to foreign body inhalation were common among this group. All 5 teenage patients presented after inhalation of small objects. 4 patients from the teenage group had general anaesthesia; in 2 of them a laryngeal mask airway was employed, whilst 2 had endotracheal intubation. Only one patient was given a rigid bronchoscopy following failure of the fiberoptic instrument. Difficulties at retrieval of foreign body were frequently encountered. Conclusions. In the adolescent and adult patients, most inhaled foreign bodies are retrievable by flexible bronchoscopy. However, facilities for rigid bronchoscopy should be available as a back-up. Pulmonary complications are common after foreign body inhalation especially in the older patients. Difficulties at bronchoscopic removal may occur due to late presentation or to the site and/or position of the foreign body within the tracheobronchial tree.